Z mikrofonem przez USA : audycje "Glosu Ameryki" - Swiecicki, Marek (Warszawa : Oficyna Wydawnicza RYTM : Oficyna Wydawnicza POKOLENIE, 1991)
Radio essays on the United States, especially its foreign policy.
Keywords: United States -- Foreign relations -- 20th century; United States -- Economic conditions -- 20th century; United States -- Politics and government -- 20th century